2015
DOI: 10.1016/j.ijheh.2015.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of urinary phthalate metabolites and daily phthalate intakes among Japanese families

Abstract: 1We measured urinary phthalate metabolites, including di-n-butyl phthalate (DnBP), di-isobutyl 2 phthalate, benzyl butyl phthalate (BBzP), and di(2-ethylhexyl) phthalate (DEHP), from 178 school-3 aged children and their 284 family members using gas chromatography-mass spectrometry, and we 4 calculated daily phthalate intakes. The highest median levels of phthalate metabolites were for 5 mono-isobutyl phthalate in all participants except schoolchildren, where the highest levels were for 6 mono-(2-ethyl-5-oxohex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
5
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 46 publications
5
37
5
2
Order By: Relevance
“…The geometric median concentration of MEHP in our study was similar to that reported in an American study on children [24]. The sum of DEHP metabolites was considerably lower in our study than in those conducted in Australia [25], Greece [26], Denmark [27], and Japan [28] and other studies conducted in Taiwan after a food scandal [29]; however, the results were similar to those obtained in China [30]. The MnBP concentration in our study was markedly higher than that reported in a Japanese study [28] and mildly lower than that reported in a Chinese study [30].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The geometric median concentration of MEHP in our study was similar to that reported in an American study on children [24]. The sum of DEHP metabolites was considerably lower in our study than in those conducted in Australia [25], Greece [26], Denmark [27], and Japan [28] and other studies conducted in Taiwan after a food scandal [29]; however, the results were similar to those obtained in China [30]. The MnBP concentration in our study was markedly higher than that reported in a Japanese study [28] and mildly lower than that reported in a Chinese study [30].…”
Section: Discussionsupporting
confidence: 88%
“…The sum of DEHP metabolites was considerably lower in our study than in those conducted in Australia [25], Greece [26], Denmark [27], and Japan [28] and other studies conducted in Taiwan after a food scandal [29]; however, the results were similar to those obtained in China [30]. The MnBP concentration in our study was markedly higher than that reported in a Japanese study [28] and mildly lower than that reported in a Chinese study [30]. The sum of DBP metabolite concentrations in our study was similar to that reported in America [24] but lower than that reported in Australia [25], Denmark [27], Germany [21], and Greece [26].…”
Section: Discussioncontrasting
confidence: 75%
“…The results obtained were compared with those for previous studies targeting Japan. The levels of the urinary concentrations of MMP, MEP, MiBP, MnBP, MBzP and MECPP in this study approximately agreed with those from the previous reports, namely 6.5–33 μg/L as the median of urinary concentrations for MMP, 6–18 μg/L for MEP, 8.4 μg/L for MiBP, 15.7–60.0 μg/L for MnBP, 2.4–18.3 μg/L for MBzP and 7.5–44.1 μg/L for MECPP (Bamai et al, ; Guo et al, ; Itoh, Yoshida, & Masunaga, ; Kato et al, ; Kondo et al, ; Suzuki et al, ). On the other hand, urinary McHP had not been detected previously in Japanese subjects, and furthermore, there was no detection of urinary McHP by GC/MS.…”
Section: Resultssupporting
confidence: 91%
“…Approximately 10% of the children in that study ( n = 178, age 3–12) exceeded the reference dose of 20 µg kg −1 day −1 . Interestingly, pre‐school children (age ≤ 6) often show higher daily estimated intakes than school children (age 7–14), as reported by studies in Japan, Taiwan and Germany . Most intake of phthalate is from food, but the researchers believed that playing on the ground, lying down near plastic carpet and mouthing some plastic items such as toys result in pre‐school children having relatively higher exposure than school children .…”
Section: The Plasticizer Adulteration Incident In Taiwanmentioning
confidence: 93%
“…Most intake of phthalate is from food, but the researchers believed that playing on the ground, lying down near plastic carpet and mouthing some plastic items such as toys result in pre‐school children having relatively higher exposure than school children . Furthermore, a relatively higher rate of metabolism of phthalate is found in pre‐school children than in school children as well as other age groups, so metabolism of phthalate may be an age‐dependent process …”
Section: The Plasticizer Adulteration Incident In Taiwanmentioning
confidence: 99%